A nano-graphite cold cathode for an energy-efficient cathodoluminescent light source - Obraztsov, Alexander N.; Kleshch, Victor I.; Smolnikova, Elena A. (Beilstein Journal of Nanotechnology, 2013)
The development of new types of light sources is necessary in order to meet the growing demands of consumers and to ensure an efficient use of energy. The cathodoluminescence process is still under-exploited for light generation because of the lack of cathodes suitable for the energy-efficient production of electron beams and appropriate phosphor materials. In this paper we propose a nano-graphite film material as a highly efficient cold cathode, which is able to produce high intensity electron beams without energy consumption. The nano-graphite film material was produced by using chemical vapor deposition techniques. Prototypes of cathodoluminescent lamp devices with a construction optimized for the usage of nano-graphite cold cathodes were developed, manufactured and tested. The results indicate prospective advantages of this type of lamp and the possibility to provide advanced power efficiency as well as enhanced spectral and other characteristics.
Keywords: cathodoluminescence; electron field emission; light source; nano-graphite; vacuum electronics